2020
DOI: 10.33992/jgk.v13i1.1134
|View full text |Cite
|
Sign up to set email alerts
|

Spa kaki dengan Bantuan Kayu Refleksi terhadap Saturasi Oksigen pada Diabetesi

Abstract: Foot Spa with the Help of Wood Reflections on Oxygen Saturation in People withDiabetes. The study was conducted with a quasi-experimental method, pre-test post test with control group design. The study used 2 (two) groups, group I was given treatment in the form of Foot SPA with the help of wood reflection every 2 days 15-30 minutes for 6 weeks, group II (control group) were given foot exercises every 2 days 15-30 minutes for 6 weeks. Saturation data were collected with digital oximetry at the beginning of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
0
3
0
2
Order By: Relevance
“…The cardiovascular response to spinal anesthesia results from sympathetic nerve block induced by intrathecal local anesthetics. The sympathetic block causes a total loss of venous tone, leading to a decrease in cardiac output and a reduction in blood pressure ( 28 , 29 ). In this study, we found a decrease in systolic and diastolic blood pressure means and MAP after anesthesia induction in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…The cardiovascular response to spinal anesthesia results from sympathetic nerve block induced by intrathecal local anesthetics. The sympathetic block causes a total loss of venous tone, leading to a decrease in cardiac output and a reduction in blood pressure ( 28 , 29 ). In this study, we found a decrease in systolic and diastolic blood pressure means and MAP after anesthesia induction in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Based During the massage process, VCO will bind to sweat which then coats the surface of the skin and holds water in the stratum corneum. The retention of water in the stratum corneum will keep the skin moist and reduce itching on the skin as well (Daryaswanti, 2018;Sukawana et al, 2020;Zuryati, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…endorphins, and growth hormone. Where these hormones will cause disruptions in controlling blood sugar levels (Sukarja, Sukawana, & Suyasa, 2014). It is further explained that stress can increase blood sugar content because stress can stimulate endocrine organs to secrete epinephrine which has a very strong effect in causing the process of glyceogenesis in the liver so that it will release a large amount of glucose in the blood in a few minutes.…”
Section: Family Supportmentioning
confidence: 99%